Photang thrust sheet: an accretionary complex structurally below the Spontang ophiolite constraining timing and tectonic environment of ophiolite obduction, Ladakh Himalaya, NW India (Geological Society Publishing House, 1999)
The pre-collisional tectonic evolution of the north Indian continental margin is best recorded in the few ophiolite complexes preserved, the largest of which occurs in the Spontang area of the Himalayas. Structural, sedimentological, palaeontological and geochemical work on the ophiolite and associated allochthonous thrust sheets has been carried out to constrain the timing and tectonic environment of ophiolite obduction. A distinct thrust sheet of accretionary complex rocks has been identified immediately underlying the ophiolite. Accreted units include thrust slices of tectonic melanges and alkaline basaltic lavas capped by limestones ranging from late Permian to late Cretaceous in age, interpreted as remnants of former seamounts. The accretionary complex formed above a north dipping intra-oceanic subduction zone during the Cretaceous, the Spontang ophiolite located in the hanging wall. Beneath the Photang thrust sheet, two further distinct, allochthonous thrust sheets of sedimentary melanges and continental slope deposits have been recognized. The structural relations of the allochthonous thrust sheets with the sediments of the north Indian margin have been mapped in detail and show clear evidence that obduction occurred in the late Cretaceous. At this time the Dras-Kohistan intra-oceanic arc had already collided with the southern Asian margin, over 1500 km to the north. Obduction of the Spontang ophiolite therefore records a separate tectonic episode in the Ladakh Himalaya.